Pengaruh Green Bond dan Green Budget Tagging terhadap Pembangunan Berkelanjutan di Indonesia - Elmira Siska; Rini Larasati Irawan; Tri Lestari; Sri Rahayu; Alya Kanaya Alfita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Sustainable development is one of the main priorities in an effort to maintain a balance between economic growth, environmental sustainability, and social welfare. Green financial instruments such as Green Bonds and the implementation of Green Budget Tagging have emerged as important strategies in supporting the sustainable development agenda in Indonesia. This study aims to analyze the effect of green bonds and green budget tagging on the achievement of sustainable development. The method used is a quantitative approach with regression analysis, where green bonds and green budget tagging are independent variables, while sustainable development is the dependent variable. The data used are annual time series data from 2018-2023. Data processing was carried out using the SPSS 25 program. The results of the study indicate that partially Green Bonds do not have a significant effect on sustainable development in Indonesia (statistical t significance value 0.970 > 0.05). Green Budget Tagging has a significant effect on sustainable development in Indonesia (statistical t significance value 0.021 < 0.05). Simultaneously, both variables significantly influence sustainable development in Indonesia (F-statistic significance value 0.034 < 0.05). This finding indicates that optimizing green bond issuance and implementing green budget tagging can strengthen green financing and ensure budget allocation is more focused on sustainable programs. The implications of this research emphasize the importance of the government and related institutions' commitment to expanding green financial instruments as a key pillar in supporting inclusive and environmentally sound development in Indonesia.